Od karte do lokalne topografske baze - Vešligaj, Staško (Geodetski vestnik, 1998)
The basic principles of establishing topographic databases in the local community of Maribor are discussed, along with the main reasons for doing so. The significance and role of external institutions concerned with the maintenance of various databases (utilities) is enphasised, as well as the way these institutions are involved in the process of further developing and maintaining of the local topographic database in Maribor. The basic methodological approach to identification and definition of individual objects in the local topographic database is also described.
Keywords: geodezija; Slovenija; topografija; topografske baze